Occurrence of Winged Forms of Atta sexdens rubropilosa Forel (Hymenoptera: Formicidae) in Laboratory Colonies - BUENO,ODAIR C. (2002)
The production of hundreds of reproductive forms of Atta sexdens rubropilosa Forel in nests maintained in laboratory was observed for the first time in Brazil. Last instar male larvae were found on August 5, 2000 in a six-year-old colony with approximately 110 L of fungus garden distributed in 21 pots. Thirty to forty days later, queen larvae started to be seen. The adult sexual forms were comparable in size with those found in the field. Two apparent failed attempts of a nuptial flight were observed during the last week of October, followed by the appearance of dead males and females in the garbage piles of the colony.